3(x+2)+2=5x+2(x-2)

Simple and best practice solution for 3(x+2)+2=5x+2(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)+2=5x+2(x-2) equation:


Simplifying
3(x + 2) + 2 = 5x + 2(x + -2)

Reorder the terms:
3(2 + x) + 2 = 5x + 2(x + -2)
(2 * 3 + x * 3) + 2 = 5x + 2(x + -2)
(6 + 3x) + 2 = 5x + 2(x + -2)

Reorder the terms:
6 + 2 + 3x = 5x + 2(x + -2)

Combine like terms: 6 + 2 = 8
8 + 3x = 5x + 2(x + -2)

Reorder the terms:
8 + 3x = 5x + 2(-2 + x)
8 + 3x = 5x + (-2 * 2 + x * 2)
8 + 3x = 5x + (-4 + 2x)

Reorder the terms:
8 + 3x = -4 + 5x + 2x

Combine like terms: 5x + 2x = 7x
8 + 3x = -4 + 7x

Solving
8 + 3x = -4 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
8 + 3x + -7x = -4 + 7x + -7x

Combine like terms: 3x + -7x = -4x
8 + -4x = -4 + 7x + -7x

Combine like terms: 7x + -7x = 0
8 + -4x = -4 + 0
8 + -4x = -4

Add '-8' to each side of the equation.
8 + -8 + -4x = -4 + -8

Combine like terms: 8 + -8 = 0
0 + -4x = -4 + -8
-4x = -4 + -8

Combine like terms: -4 + -8 = -12
-4x = -12

Divide each side by '-4'.
x = 3

Simplifying
x = 3

See similar equations:

| 4(3x)2/(2x)2 | | 2z^2+13z+21=0 | | (x-3)=180 | | 0=-6x^2+10x+5 | | 8r+4=-1+8r | | 3(-1)-3y=2(-1)+6 | | 6x=1.25 | | 5x-(x-2)=2x+1 | | -6k-8=-12 | | 7(x+7)-2= | | ×/3×/7×/11 | | 0.5(8x+24)=4 | | 2/3h=3/4 | | (6/8)y-12=-6 | | 8x-7*2x+6=0 | | 1=1-v+7v | | -4n+8=-3n-1 | | w/3.5=24 | | 20-100x=0 | | 9x^2-42x+c=0 | | 2X+2y-5z=-5 | | 10=10000 | | 4x-5x+11=13 | | 3(x+2)+2=5x+2(2x+2) | | 0.333333333333(x-9)=18 | | 45-3y=6y | | 11xn=490061 | | log(7)y=-2 | | X=27-13 | | 42+w=8w | | -10y-19=19-8y | | P=M(1+dn) |

Equations solver categories